PENGARUH MOTIVASI PELAYANAN PUBLIK, KUALITAS PELAYANAN DAN KINERJA ANGGOTA TERHADAP KEPUASAN MASYARAKAT PADA POLSEK KOTA SUNGAI PENUH - Helmi Ali; Yudi Stira (JEBIM Prima, 2022)
This study aims to determine the effect of public service motivation, service quality, and performance of police officers on community satisfaction with members of the Sungai Penuh City Police. The method used in this research is quantitative research with a descriptive approach. The population in this study were members of the police at the Sungai Penuh Police. The sample used was 144 people using a saturated sampling technique (census). The data analysis technique is multiple linear regression. The results of the study show that: (1) Public service motivation has a positive and significant effect on community satisfaction. (2) Service quality has a positive and significant effect on community satisfaction. (3) The performance of police officers has a positive and significant effect on community satisfaction. (4) Public service motivation, service quality, performance of police officers together have a positive and significant effect on community satisfaction at the Sungai Full Police Sector.